Implementasi Service EC2 & S3 Amazon Web Service Pada Niche Blog Menggunakan Metode SDLC - Yudha Harimurti; Devi Udariansyah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Currently, cloud computing (Cloud Computing) plays an important role in the development of technology. because the problem of data storage is always a problem. Cloud computing is a client-server model where resources such as servers, storage, networks and software are considered as services that can be accessed by users anytime and anywhere. Organizations or companies can use this information technology service to run their business in a way that is easier for users. Today, there are many cloud computing platforms available, and Amazon Web Services (AWS) is one of the largest cloud service providers in the world with the highest run rate of almost USD 10 billion. Elastic Compute Cloud (EC2) and Simple Storage Service (S3) are two cloud computing technologies provided by Amazon Web Service (AWS). Hosting a NICHE BLOG site is one way Elastic Compute Cloud (EC2) and Simple Storage Service (S3) are used together. These various cloud computing services make it possible to store, manage and display content in an effective and efficient manner. The closing of this research is a blog post that runs on Amazon Web Services Elastic Compute Cloud (EC2). This research aims to explain the role of Elastic Compute Cloud (EC2) and Simple Storage Service (S3) in blog posts using the Software Development Life Cycle (SDLC) method.